2013
DOI: 10.1093/inthealth/iht030
|View full text |Cite
|
Sign up to set email alerts
|

Personal experiences and attitudes towards intimate partner violence in healthcare providers in Guyana

Abstract: This study demonstrates a high prevalence of IPV among HCWs and identifies prevailing attitudes regarding IPV. This knowledge is essential in developing effective, appropriate training programs and identifies a need to address IPV among the healthcare workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…They found that, in the last 12 months, 12.2% of nurses had experienced non-physical abuse by a partner, while 3.1% had been physically abused, and these were substantially increased rates to that of the general community [ 26 ]. The limitations of the few studies on this issue include: a lack of rigor in the assessment of IPV [ 12 , 14 , 16 , 17 , 20 , 22 ], low or unpublished response rates [ 20 , 23 , 26 ], small sample sizes [ 21 , 23 , 24 ], or publication ten or more years ago [ 15 17 , 24 , 25 ]. Another feature of these studies is their diversity: six of the studies were conducted in countries where a language other than English is the official language [ 15 , 16 , 18 , 19 , 21 , 23 ], and in some countries prevalence studies were hard to generalise to the Australian context since the population prevalence was substantially higher than reported in the Australian community [ 18 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that, in the last 12 months, 12.2% of nurses had experienced non-physical abuse by a partner, while 3.1% had been physically abused, and these were substantially increased rates to that of the general community [ 26 ]. The limitations of the few studies on this issue include: a lack of rigor in the assessment of IPV [ 12 , 14 , 16 , 17 , 20 , 22 ], low or unpublished response rates [ 20 , 23 , 26 ], small sample sizes [ 21 , 23 , 24 ], or publication ten or more years ago [ 15 17 , 24 , 25 ]. Another feature of these studies is their diversity: six of the studies were conducted in countries where a language other than English is the official language [ 15 , 16 , 18 , 19 , 21 , 23 ], and in some countries prevalence studies were hard to generalise to the Australian context since the population prevalence was substantially higher than reported in the Australian community [ 18 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this topic should be reexamined in the future. From earlier studies, several risk factors for IPV have been found: low dissatisfaction with family relationships (Lee, Stefani, & Park, ), heavy drinking (Lee et al., ), older age (Mitchell, Parekh, Russ, Forget, & Wright, ), lower educational level (Tran et al., ), unemployment (Uthman, Lawoko, & Moradi, ), male‐dominant cultural background (Jewkes et al., ), and parental violence (Fleming et al., ). These findings will provide the information necessary for nurses in the hospital or community setting to organize prevention programs for IPV.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive search of the academic literature (1991-2021) using the search (and associate) terms – ‘intimate partner violence’; ‘domestic violence’; ‘family violence’; ‘nurses and health professionals’ – identified 19 quantitative studies about DFV against nurses globally [ 8 , 9 , 16 – 32 ]. Originating from 16 countries, most of these studies report DFV prevalence against women nurses, with five studies including men nurses [ 8 , 18 , 21 , 24 , 29 ]. Of two studies that separate the experience of IPV during the last 12-month by gender, men nurses reported a higher prevalence of combined IPV (between 9 and 16%) than women nurses (between 8.2 and 13.9%), which was not consistent with local community statistics [ 8 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Originating from 16 countries, most of these studies report DFV prevalence against women nurses, with five studies including men nurses [ 8 , 18 , 21 , 24 , 29 ]. Of two studies that separate the experience of IPV during the last 12-month by gender, men nurses reported a higher prevalence of combined IPV (between 9 and 16%) than women nurses (between 8.2 and 13.9%), which was not consistent with local community statistics [ 8 , 24 ]. In the three studies of adult lifetime IPV however, women reported a higher combined IPV prevalence (between 34 and 51%) than men (between 3 and 21%) [ 18 , 24 , 29 ].…”
Section: Introductionmentioning
confidence: 99%